2014
DOI: 10.1371/journal.pone.0085363
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Control Region Alterations and Breast Cancer Risk: A Study in South Indian Population

Abstract: BackgroundMitochondrial displacement loop (D-loop) is the hot spot for mitochondrial DNA (mtDNA) alterations which influence the generation of cellular reactive oxygen species (ROS). Association of D-loop alterations with breast cancer has been reported in few ethnic groups; however none of the reports were documented from Indian subcontinent.MethodologyWe screened the entire mitochondrial D-loop region (1124 bp) of breast cancer patients (n = 213) and controls (n = 207) of south Indian origin by PCR-sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 41 publications
2
41
1
Order By: Relevance
“…In addition, it may be used as clonal marker for solid tumors (38). The T16189C variation has been reported in breast (39) and endometrial (40) cancer, and the (CA) n repeat was associated with breast cancer survival rate (41). However, they have not been reported in patients with AML, and in the present study, no association was identified between the aforementioned variations and AML risk, which may be due to the different underlying pathogenesis of different cancer types.…”
Section: Patients With Aml-m3 (T152c Variationmentioning
confidence: 99%
“…In addition, it may be used as clonal marker for solid tumors (38). The T16189C variation has been reported in breast (39) and endometrial (40) cancer, and the (CA) n repeat was associated with breast cancer survival rate (41). However, they have not been reported in patients with AML, and in the present study, no association was identified between the aforementioned variations and AML risk, which may be due to the different underlying pathogenesis of different cancer types.…”
Section: Patients With Aml-m3 (T152c Variationmentioning
confidence: 99%
“…In addition, the most frequent DNA alterations in the mitochondrial genome were reported in the hypervariable segment-1 (HSV1, np 16204-16383) and -2 (np 57-373) of the CR, which were mostly located in the D-loop, at various types of tumors such as head and neck, colorectal, lung, bladder, melanoma, uterine cervix and breast cancer (Ashtiani et al, 2012;Cai et al, 2011;Zhang et al, 2015). Further associations were also established between single nucleotide polymorphisms (SNPs) of the CR and various complex diseases such as; metabolic syndrome, type II diabetes mellitus (DM), neurodegenerative diseases and aging in literature (Ghezzi et al, 2005;Guney et al, 2014;Mueller et al, 2011;Tipirisetti et al, 2014;Zhang et al, 2015). But, some of the findings are still debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria play a central role in variety of cellular processes including metabolism, ATP production, calcium homeostasis and apoptosis (Tipirisetti et al, 2014). Shifting in glucose metabolism from OXPHOS to glycolysis has been observed in cancer cells nearly a century ago by Otto Warburg and he proposed that tumor cells, unlike the normal one, display highly glycolytic activity even in the presence of abundant oxygen for mitochondria to produce ATP by means of oxidative phosphorylation (Warburg et al, 1927).…”
Section: Introductionmentioning
confidence: 99%
“…These two factors are especially important in the context of prevalence of various kinds of cancer [1]. While it is clear that diverse genetic pathways exist for the development and progression of various cancers, the emerging evidence strongly suggests that the pathogenesis of cancer is complex and multifactorial, ranging from the environment and dietary habits to genetic and molecular alterations [2].…”
Section: Introductionmentioning
confidence: 99%